Upaya Menekan Kehilangan Hasil Produksi Kelapa Sawit pada Daerah Bukit Bergunung dan Daerah Datar Bergelombang - Riski, Dewa; Gunawan, Sri; Ardiani, Fani (Politeknik Negeri Lampung, 2023)
Oil palm is a plant that produces vegetable oil and is cultivated in various terrain, including undulating flats and mountainous hills. The aim of this study was to identify the factors causing losses in these areas and to investigate ways to reduce the production and income effects of these losses. The research was conducted at the Palm Oil Plantation of PT. Supra Matra Abadi in North Sumatra Province, using a quantitative research method. Samples were taken from blocks A, B (planted in 1988) and C, D (planted in 2016). The parameters observed included the number of losses in the circle, path, and collection point of FFB, areas, plant age, and the suitability and completeness of equipment. Treatments included spraying on circles, paths, and collection points of FFB, as well as the placement of employees based on their experience level and the provision of tools. Data analysis was conducted using the t-test to compare results before and after treatment. The study found that the highest losses occurred in mountainous hill areas, with an average of 2.394 kg.ha-1, while the lowest losses occurred in undulating flat areas, with an average of 1.420 kg.ha-1. The results also showed that losses decreased by 28.17% or 0.678 kg.ha-1 in mountainous hill areas and by 36.93% or 0.522 kg.ha-1 in undulating flat areas after treatment. The economic value of losses was IDR 2,271.30 per ha in mountainous hill areas and IDR 1,748.70 per ha in undulating flat areas. Therefore, this study concludes that the spray treatment of circles, paths, collection point of FFB, placement of employees based on their experience level, and provision of equipment significantly reduced losses in undulating flat areas and mountainous hills.